2013
DOI: 10.1152/physiolgenomics.00066.2013
|View full text |Cite
|
Sign up to set email alerts
|

Genome scan for meat quality traits in Nelore beef cattle

Abstract: Meat quality traits are economically important because they affect consumers' acceptance, which, in turn, influences the demand for beef. However, selection to improve meat quality is limited by the small numbers of animals on which meat tenderness can be evaluated due to the cost of performing shear force analysis and the resultant damage to the carcass. Genome wide-association studies for Warner-Bratzler shear force measured at different times of meat aging, backfat thickness, ribeye muscle area, scanning pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
4
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(183 citation statements)
references
References 54 publications
(49 reference statements)
6
165
4
7
Order By: Relevance
“…Samples were filtered based on a call rate [12] greater than 85% and heterozygosity greater than 40%. Loci were deleted if their Illumina probe sequence could not be uniquely mapped to an autosome on the UMD3.1 reference assembly [13], if their call rate was less than 90%, minor allele frequency was less than 0.5%, or if they deviated severely from Hardy Weinberg equilibrium (χ 2 > 100.0), as described by Tizioto et al [2]. Only autosomal genotypes were used in the association analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were filtered based on a call rate [12] greater than 85% and heterozygosity greater than 40%. Loci were deleted if their Illumina probe sequence could not be uniquely mapped to an autosome on the UMD3.1 reference assembly [13], if their call rate was less than 90%, minor allele frequency was less than 0.5%, or if they deviated severely from Hardy Weinberg equilibrium (χ 2 > 100.0), as described by Tizioto et al [2]. Only autosomal genotypes were used in the association analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on the Nelore cattle population used here [2,3] and on other Bos taurus populations [4] have suggested that muscle mineral content may influence beef quality traits, such as meat tenderness, possibly because the effect of the genes that control these traits depends on the presence of specific minerals. For example, reduced calcium availability may affect the calpain-calpastatin system, which plays a major role in postmortem proteolysis and meat tenderization [5-7], as well as being crucial for muscle contraction.…”
Section: Introductionmentioning
confidence: 99%
“…This trait is particularly relevant for Bos indicus breeds, such as Nelore, which are known to produce less tender meat. However, recent studies have shown that it has sufficient variability to be included in animal breeding programs (Tizioto et al, 2013a;Tonussi et al, 2015). In addition, it is a complex trait involving many genes, including KCNJ11 (potassium inwardly rectifying channel, subfamily J, member 11), which was recently associated with beef tenderness (Tizioto et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the CNVR 2280 is located 627.14 kb downstream of a previously described QTL for MT in this Nelore population (TIZIOTO et al, 2013), which overlap the three detected GSTA genes.…”
Section: Cnvr 1541mentioning
confidence: 52%
“…Further, CNVR 1541 and 2280 are in the vicinity of QTLs for MT in this Nelore population (TIZIOTO et al, 2013 CNVR 1541 show significant influence on gene expression in its neighborhood considering the combined P-value of all CNVFs detected in this region. From those, 9…”
Section: Impact Of Mt-cnvrs On Gene Expressionmentioning
confidence: 76%